21. THE CURRENT STATUS OF FOOD SAFETY CONDITIONS OF FOOD SERVICE FACILITIES AND TO IDENTIFY SOME RELATED FACTORS IN HAI HA DISTRICT, QUANG NINH PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current status of food safety conditions of food service facilities and to identify some related factors in Hai Ha district, Quang Ninh province, in 2023 Research method: A cross-sectional descriptive study was conducted with 197 registered food service facilities in Hai Ha district. Food safety conditions were assessed using a checklist developed based on Circular No. 48/2015/TT-BYT dated December 1, 2015 of the Ministry of Health. Results: 31.98% of facilities met the overall requirements for food hygiene and safety. Scale of operation, type of facilities (OR=4.67; 95% CI: 1.98-10.98), being a ready-to-eat food-providing facility (OR=0.2; 95% CI: 0.11-0.64), being inspected/inspected by the food safety authority 3 times or more in 1 year (OR=7.2; 95%CI=3.48-14.98), and being recently recognized as meeting the food safety requirements by the local food safety authority (OR=24.08; 95%CI=11.01-52.65) were factors significantly associated with the current status regarding food safety and hygiene. Conclusion: Food service establishments do not have high food hygiene and safety standards. It is necessary to supplement administrative procedures according to the provisions of law, invest in upgrading facilities, select and strictly control input materials.
Keywords: Food safety conditions, food service facilities, Quang Ninh.